2022
DOI: 10.1002/ana.26511
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐Related Imaging Abnormalities in the DIAN‐TU‐001 Trial of Gantenerumab and Solanezumab: Lessons from a Trial in Dominantly Inherited Alzheimer Disease

Abstract: Objective To determine the characteristics of participants with amyloid‐related imaging abnormalities (ARIA) in a trial of gantenerumab or solanezumab in dominantly inherited Alzheimer disease (DIAD). Methods 142 DIAD mutation carriers received either gantenerumab SC (n = 52), solanezumab IV (n = 50), or placebo (n = 40). Participants underwent assessments with the Clinical Dementia Rating® (CDR®), neuropsychological testing, CSF biomarkers, β‐amyloid positron emission tomography (PET), and magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
(137 reference statements)
0
15
1
Order By: Relevance
“…This finding has implications for clinical trial enrollment since total microhemorrhage count is a strong risk factor for the development of Aβ-related imaging abnormalities (ARIA) in individuals with DIAD treated with anti-amyloid antibodies. 49 Vascular risk factors may influence the development of these markers of SVD, but in our cohort no difference between pre-and post-200 PSEN1 carriers was observed in the prevalence of hypercholesterolemia, diabetes, or stroke. However, the prevalence of clinically confirmed hypertension was lower in the pre-200 group.…”
Section: 42contrasting
confidence: 53%
See 1 more Smart Citation
“…This finding has implications for clinical trial enrollment since total microhemorrhage count is a strong risk factor for the development of Aβ-related imaging abnormalities (ARIA) in individuals with DIAD treated with anti-amyloid antibodies. 49 Vascular risk factors may influence the development of these markers of SVD, but in our cohort no difference between pre-and post-200 PSEN1 carriers was observed in the prevalence of hypercholesterolemia, diabetes, or stroke. However, the prevalence of clinically confirmed hypertension was lower in the pre-200 group.…”
Section: 42contrasting
confidence: 53%
“…Regarding microhemorrhages, while we confirmed our previous report that mutation position does not significantly affect the odds of developing them generally 28 or in any specific lobe, we did find an influence on the total count of microhemorrhages, including a trend toward occipital count, with post‐200 carriers showing higher counts starting at preclinical stages. This finding has implications for clinical trial enrollment since total microhemorrhage count is a strong risk factor for the development of Aβ‐related imaging abnormalities (ARIA) in individuals with DIAD treated with anti‐amyloid antibodies 49 …”
Section: Discussionmentioning
confidence: 99%
“…DIAN-TU, a phase 2/3 trial, focused on primary prevention for the autosomal dominant form of AD, which has a known link to Aβ dysfunction and early cognitive decline 29 . Regrettably, a preliminary analysis of the trial revealed that both investigational anti-amyloid drugs, Roche's gantenerumab and Lilly's solanezumab, did not meet the primary endpoint criteria (DIAN-Multivariate Cognitive Endpoint) 30 . In October 2019, phase 3 study was conducted using aducanumab's which also could not offer clinical advantage and could not modify the diseases severity 31 .…”
Section: Redefining New Strategies For Managing Admentioning
confidence: 99%
“…Different incidences of ARIA have been observed in clinical trials, with ARIA-E rates of 30% or greater for aducanumab 14 , 25 , 26.7% for bapineuzumab 15 , 25% for gantenerumab 26 28 , 24% for donanemab 16 , and 12.6% for lecanemab 17 , while solanezumab and crenezumab have no reported cases of ARIA-E 29 32 . Although the molecular mechanisms underlying these differences are unclear, they are likely to relate to the profiles of antibody binding to different forms of Aβ, and to the ability of the antibody to mobilize vascular amyloid and trigger microglial effector function.…”
Section: Introductionmentioning
confidence: 99%